2018
DOI: 10.1002/agm2.12004
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of hyperuricemia in older adults in China and possible associations with sarcopenia

Abstract: Objective: This cross-sectional study aimed to investigate the characteristics and epidemiology of hyperuricemia in older adults in China and evaluate possible associations between hyperuricemia and sarcopenia.Methods: Three hundred and eighty-eight study subjects (>60 years old) meeting the inclusion criteria received blood tests and standardized examinations for bone mineral density, muscle mass, muscle strength, and physical performance. Data including demographic and clinical characteristic and comorbidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…We also observed that skeletal muscle index and grip strength were positively associated with UA level. This finding is consistent with those of previous cross-sectional studies in the elderly [31][32][33]. UA is the final product of purine metabolism.…”
Section: Discussionsupporting
confidence: 93%
“…We also observed that skeletal muscle index and grip strength were positively associated with UA level. This finding is consistent with those of previous cross-sectional studies in the elderly [31][32][33]. UA is the final product of purine metabolism.…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, higher UA level was found to have no relationship with physical performance which was assessed using Short Physical Performance Battery (SPPB) scale in another two cross-sectional study 16,17 . This might be explained by the reason that SPPB is a nal sum of multiple parameters that included walking speed over 4 meters, ve timed repeated chair rises and standing balance.…”
Section: Discussionmentioning
confidence: 90%
“…One study showed that an inverted J-shaped association between serum UA levels and HGS in both genders among Chinese adults aged over 45 5 . Another study in China showed that higher uric acid levels were signi cantly correlated with higher muscle mass, grip strength in 388 participants aged over 60 16 . Besides, study in Japan found an inverted J-shaped association between the serum UA quartiles and muscle strength in 630 male Japanese employees aged over 30 years old 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Uric acid is an enzymatic waste endproduct from the degradation of purine nucleosides that is renally excreted. Uric acid plays both protective and damaging roles in the skeletal muscles [ 39 ], most likely due to its strong antioxidant properties at low levels and pro-inflammatory effect at high levels [ 35 ]. It has been proposed that oxidative stress might contribute to muscle weakness and wasting.…”
Section: Discussionmentioning
confidence: 99%